Research design : - Creswell, John W. (SAGE Publications, 2014)
The bestseller that pioneered the comparison of qualitative, quantitative, and mixed methods research design continues in its Fourth Edition to help students and researchers prepare their plan or proposal for a scholarly journal article, dissertation or thesis.